Distributed Explicit Bounded LTL Model Checking - Krčál, Pavel (Electronic notes in theoretical computer science, 2003)
Automated formal verification becomes a significant part of an industrial design process. Favourite formal verification method  model checking  is strongly limited by the size of the model of the verified system. It suffers from the so called state explosion problem. We propose to fight this problem by applying the idea of bounding the examined state space in explicit model checking. Moreover, we combine this approach with the distribution of the computation among the network of workstations. We consider several distributed bounded LTL model checking algorithms and carry out a series of experiments to evaluate them and to compare their behaviour.